Perceived Barriers to Physical Activity and Exercise for Individuals with Spinal Cord Injury. Issue 2 (December 2014) - Keegan, John; Brooks, Jessica; Blake, John; Muller, Veronica; Fitzgerald, Sandra; Chan, Fong
Abstract : This study investigated the relationship between functional disability and perceived barriers to physical activity and exercise in persons with Spinal Cord Injury (SCI). Participants were 144 individuals with SCI (mean age was 44 years old; 61% were male participants; 41.3% had spinal cord lesion at the cervical level, 43.7% at the thoracic level, and 14.3% at the lumbar level) from the National Spinal Cord Injury Association in the United States. Data on physical activity and exercise participation were collected using a cross-sectional online survey and analysed using multivariate analysis of variance and hierarchical regression analysis. The primary research findings indicate that level of functional disability was a predictor of perceived barriers to physical activity and exercise. Moreover, health barriers were found to be a partial mediator for functional disability and physical health-related quality of life, suggesting perceived barriers may help to explain the association between functional disability and physical health-related quality of life.